The Relationship Between Early Puberty Age And Sexual Behavior On Teenage Students at SMK X Jakarta - Jiyarti Septhyaningrum; Roza Indrayeni (Universitas Prima Indonesia, 2026)
Adolescence is a transition period from childhood to adulthood. A person who has entered the adolescent age group, namely 10-19 years old, will experience puberty, rapid growth and development called Growth Spurt, physical, mental, psychological changes, reproductive organ maturity and have vulnerable behaviors that may include behaviors such as becoming addicted to alcohol, drugs and negative sexual behavior. The purpose of this study was to determine the relationship between early puberty and sexual behavior in adolescent students in grades XI and XII at SMK X Jakarta. This study was quantitative, conducted by cross-sectional method using correlation analysis as a research design. The population of this study were students in grades XI and XII of SMK X Jakarta, there were 157 students. Sampling used simple random sampling, namely 61 students. Data collection used a questionnaire analyzed by the Person Chi-Square test. The results of this study using Chi-Square obtained a p value of 0.016 ≤ 0.05, which means it shows a significant relationship between the age of early puberty and sexual behavior in adolescent students at SMK X South Jakarta. Based on the results it can be concluded that there is a significant relationship between the age of puberty and sexual behavior in adolescent students at SMK X South Jakarta (p value = 0.016 ≤ 0.05).